Factors Affecting Nurses’ Perceived Organizational Commitment: A Qualitative Study (Bangladesh Journal of Medical Science, 2019)
Objective: Nurses’ organizational commitment is one of the most important factors that facilitates their professional evolution and influences the method of care provision, quality of care, and patients’ satisfaction. The aim of this study was identified the factors that affect nurses’ perceived organizational commitment.Material and Methods: This qualitative study, conducted on 16 clinical nurses employed in Social Security Hospital of Khorramabad, Iran, during five months from May to September 2015, used deep semi-structured interviews. Purposive sampling method was used for the selection of nurses and the data were analyzed using conventional qualitative content analysis. Lincoln & Guba’s criteria were used to secure data accuracy and stability.Results: Sixteen subcategories, five categories, and three themes were distilled during content analysis process. The abstracted themes included “organizational factors”, “occupational challenges”, and “contributory management”.Conclusion: Our findings showed that numerous factors present in nurses’ profession and work environment may influence the rate of nurses’ interest and commitment in the hospital and the related organization. Hence, nurse managers can foster the promotion of nurses’ organizational commitment through creating the required suitable conditions.Bangladesh Journal of Medical Science Vol.18(2) 2019 p.303-311